Opium Addiction And Its Management With Ayurveda – A Case Report - Aara, Noori; Upadhyay, Parmanand; Godara, Sunita; Ansari, Mohd Adil; Kumar, Amit (International Research Journal of Ayurveda & Yoga, 2020)
Opiate addiction gives physical and mental toxic effect along with inhibition of morality and social awareness. It is difficult to stop time dependency. One, opium (doda-posta) addicted patient taking opium since 5years and presented with Anxity, insomnia, chest pain, nausea, diarrhoea, loss of appetite and slight tremor. The patient was treated with Nashamukti Yog 3 (Kalpit yog), Ashavgandha Churna, Shatavari Churna, Chopchini Churna, Bilva churna, Yograj Guggulu, Shirodhara with Mansyaadi Kuwath and Abhyanga with Mahanarayan tail. The treatment approaches to improve in condition of patient with improvement in sign and symptoms of opium dependency and symptoms withdrawal. The result assessment is done on the basis of COWS score.